2019
DOI: 10.1093/bioinformatics/btz207
|View full text |Cite
|
Sign up to set email alerts
|

CliqueMS: a computational tool for annotating in-source metabolite ions from LC-MS untargeted metabolomics data based on a coelution similarity network

Abstract: Motivation The analysis of biological samples in untargeted metabolomic studies using LC-MS yields tens of thousands of ion signals. Annotating these features is of the utmost importance for answering questions as fundamental as, e.g. how many metabolites are there in a given sample. Results Here, we introduce CliqueMS, a new algorithm for annotating in-source LC-MS1 data. CliqueMS is based on the similarity between coelution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 34 publications
(46 reference statements)
0
72
0
Order By: Relevance
“…The hypotheses of metabolite neutral masses are scored based on the matching results and optionally the empirical frequency of the adducts. 9,19 From these scores the most plausible neutral mass is returned as the result. Our data suggest that the performance of such algorithms can be improved by having a more complete adduct list generated from COVINA ( Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypotheses of metabolite neutral masses are scored based on the matching results and optionally the empirical frequency of the adducts. 9,19 From these scores the most plausible neutral mass is returned as the result. Our data suggest that the performance of such algorithms can be improved by having a more complete adduct list generated from COVINA ( Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…6 The annotation step recognizes and annotates the adduct ions and natural isotopic ions. [7][8][9] These data processing steps dramatically reduce the complexity of the metabolomics data. Mahieu et al reported the analysis of an E. coli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] However, the annotation and identification of the thousands of features typically detected in LC-MS experiments remains a critical challenge. [6][7][8] It is well known that in addition to molecular ions, LC-MS 1 data also contains adducts, isotopes, multimers, in-source fragments, and contaminants, etc., which can significantly impact annotation. 6,7,9 In-source fragmentation (ISF) is a naturally occurring phenomenon in atmospheric ion sources.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] It is well known that in addition to molecular ions, LC-MS 1 data also contains adducts, isotopes, multimers, in-source fragments, and contaminants, etc., which can significantly impact annotation. 6,7,9 In-source fragmentation (ISF) is a naturally occurring phenomenon in atmospheric ion sources. [10][11][12][13] ESI is considered among the softest ionization technologies with the least ISF, however, even in the ESI source, unintentional ISF widely exists.…”
Section: Introductionmentioning
confidence: 99%